Teleclinical Microbiology: An Innovative Approach to Providing Web-Enabled Diagnostic Laboratory Services in Syria. Issue 4 (13th October 2021) - Karah, Nabil; Antypas, Konstantinos; Al-toutanji, Anas; Suveyd, Usama; Rafei, Rayane; Haraoui, Louis-Patrick; Elamin, Wael; Hamze, Monzer; Abbara, Aula; Rhoads, Daniel D; Pantanowitz, Liron; Uhlin, Bernt Eric
Abstract: Objectives: Telemedicine can compensate for the lack of health care specialists in response to protracted humanitarian crises. We sought to assess the usability of a teleclinical microbiology (TCM) program to provide diagnostic services in a hard-to-reach region of Syria. Methods: A semimobile station was equipped with conventional micrograph and macrograph digital imaging systems. An electronic platform (Telemicrobiology in Humanitarian Crises, TmHC) was created to facilitate sharing, interpreting, and storing the results. A pilot study was conducted to identify the bacterial species and antimicrobial susceptibility pattern of 74 urinary clinical isolates. An experience survey was conducted to capture the feedback of 8 participants in the program. Results: The TmHC platform (https://sdh.ngo/tmhc/ ) enabled systematic transmission of the laboratory records and co-interpretation of the results. The isolates were identified as Escherichia coli (n = 61), Klebsiella pneumoniae (n = 12), and Proteus mirabilis (n = 1). All the isolates were multidrug resistant. The performance of our TCM module was rated 4 (satisfying) and 5 (very satisfying) by 6 and 2 users, respectively. Data security of and cost-effectiveness were the main perceived concerns. Conclusions: Although we encountered several context-related obstacles, our TCM program managed to reach a highly vulnerable population of 4 million people confined in the northwest region of Syria.